Evaluating the equity of access to community health service centers in different regions of China based on cyclability and walkability - Xu, Zhenhua; Chang, Jiaying; Han, Cong (Frontiers in Public Health, 2025)
With China’s rapid urbanization and aging population, ensuring equitable access to essential facilities in Community Health Service Centers (CHSCs) is critical for delivering primary healthcare to older adults. These centers serve as the frontline for managing chronic diseases, promoting healthy aging, and reducing healthcare disparities among the older adults. This study investigates the equity of CHSCs across eastern, central, and western regions of China using indicators of cyclability and walkability, both of which are essential for older populations who often rely on active travel modes due to physical or economic limitations. A total of 110 nationally ranked CHSCs were selected for analysis. Geographic Information System (GIS) technology was used to assess cyclability, defined by a 1,000-meter residential area coverage, and walkability, represented by the average Walk Score. Results show that the cyclability scores for the eastern, central, and western regions were 0.71, 0.64, and 0.46, respectively, below the national standard of a 1,000-meter service radius, highlighting insufficient cycling access to primary care for older residents. Walkability scores were 0.351, 0.388, and 0.287, with lower values, particularly concerning aging populations with limited mobility. These findings reveal pronounced regional disparities and point to the need for spatial optimization of CHSCs, increased facility provision, and targeted resource allocation to western regions. By enhancing the active accessibility of community healthcare services, particularly for older adults, this research provides policy-relevant evidence to advance equity, promote healthy aging, and support sustainable public health planning in China.